2012
DOI: 10.1007/s10295-012-1186-x
|View full text |Cite
|
Sign up to set email alerts
|

Arabinose is metabolized via a phosphoketolase pathway in Clostridium acetobutylicum ATCC 824

Abstract: In this report, a novel zymogram assay and coupled phosphoketolase assay were employed to demonstrate that Clostridium acetobutylicum gene CAC1343 encodes a bi-functional xylulose-5-P/fructose-6-P phosphoketolase (XFP). The specific activity of purified recombinant XFP was 6.9 U/mg on xylulose-5-P and 21 U/mg on fructose-6-P, while the specific activity of XFP in concentrated C. acetobutylicum whole-cell extract was 0.094 and 0.52 U/mg, respectively. Analysis of crude cell extracts indicated that XFP activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…This is involved in the conversion of carbon compounds in fatty acids (Ellis et al, 2008;Servinsky et al, 2012), and their higher diversity suggests Prevotella has a greater repertoire of enzymes involved in this process and supports previous reports that Prevotella species are among those (including Clostridium species) that play a role in biohydrogenation of dietary polyunsaturated fatty acids to saturated fatty acids (Huws et al, 2011). This would suggest that fatty acids may be a resource for which these organisms compete and for which they have diversified niches.…”
Section: Metabolic Adaptations In Prevotellasupporting
confidence: 83%
“…This is involved in the conversion of carbon compounds in fatty acids (Ellis et al, 2008;Servinsky et al, 2012), and their higher diversity suggests Prevotella has a greater repertoire of enzymes involved in this process and supports previous reports that Prevotella species are among those (including Clostridium species) that play a role in biohydrogenation of dietary polyunsaturated fatty acids to saturated fatty acids (Huws et al, 2011). This would suggest that fatty acids may be a resource for which these organisms compete and for which they have diversified niches.…”
Section: Metabolic Adaptations In Prevotellasupporting
confidence: 83%
“…These bacteria ferment polysaccharides from plant detritus, including sugars from cellulose and hemicellulose, into acids and solvents (1)(2)(3)(4)(5). The model organism Clostridium acetobutylicum and other Clostridium species are of considerable commercial interest because of their ability to produce hydrogen gas, acetone, butanol, and ethanol from lignocellulosic components (6)(7)(8).…”
mentioning
confidence: 99%
“…Historically, it was assumed that carbons from Xyl and Arab pass from the PPP through glycolysis to supply acidogenesis and solventogenesis. However, two recent studies (5,13) reported that acids and solvents can be produced from these sugars from a glycolysis-independent pathway, the phosphoketolase pathway (PKP) (Fig. 1B).…”
mentioning
confidence: 99%
See 2 more Smart Citations